The Roles of Several Residues of Escherichia coli DNA Photolyase in the Highly Efficient Photo-Repair of Cyclobutane Pyrimidine Dimers - Lei Xu; Guoping Zhu (Journal of Nucleic Acids)
Escherichia coli DNA photolyase is an enzyme that repairs the major kind of UV-induced lesions, cyclobutane pyrimidine dimer (CPD) in DNA utilizing 350–450 nm light as energy source. The enzyme has very high photo-repair efficiency (the quantum yield of the reaction is ~0.85), which is significantly greater than many model compounds that mimic photolyase. This suggests that some residues of the protein play important roles in the photo-repair of CPD. In this paper, we have focused on several residues discussed their roles in catalysis by reviewing the existing literature and some hypotheses.